Multidisciplinary Approach in the Early Detection of Undiagnosed Connective Tissue Diseases in Patients With Interstitial Lung Disease: A Retrospective Cohort Study - Tirelli, Claudio; Morandi, Valentina; Valentini, Adele; La Carrubba, Claudia; Dore, Roberto; Zanframundo, Giovanni; Morbini, Patrizia; Grignaschi, Silvia; Franconeri, Andrea; Oggionni, Tiberio; Marasco, Emiliano; De Stefano, Ludovico; et al. (Frontiers in Medicine, 2020)
Interstitial Lung Disease (ILD) encompasses a wide range of parenchymal lung pathologies with different clinical, histological, radiological and serological features. Follow-up, treatment, and prognosis are strongly influenced by the underlying pathogenesis. Considering that an ILD may complicate the course of any connective tissue disease (CTD) and that CTD’s signs are not always easily identifiable, it could be useful to screen every ILD patient for a possible CTD. The recent definition of Interstitial Pneumonia with Autoimmune Features (IPAF) is a further confirmation of the close relationship between CTD and ILD. In this context, the multidisciplinary approach is assuming a growing and accepted role in the correct diagnosis and follow-up, in order to as early as possible define the best therapeutic strategy. However, despite clinical advantages, till now, the pathways of the multidisciplinary approach in ILD patients are largely heterogeneous across different centres and the best strategy to apply is still to be established and validated. Aims of this article are to describe the organization of our Multidisciplinary Group for ILD, which is mainly focused on the early identification and management of CTD in patients with ILD, and to show our results in a 1-year period of observation. We found that 15% of patients referred for ILD had an underlying CTD, 33% had IPAF and 52% had ILD without detectable CTD. Furthermore, we demonstrated that the adoption of a standardized strategy consisting of a screening questionnaire, specific laboratory tests and nailfold videocapillaroscopy in all incident ILD proved useful in making the right diagnosis.